The Importance of Enzyme Inhibition Kinetics for the Effect of Thrombin Inhibitors in a Rat Model of Arterial Thrombosis - Elg, Margareta; Gustafsson, David; Deinum, Johanna (Thrombosis and Haemostasis, 1997)
The relation between the antithrombotic effect in vivo, and the inhibition constant (Ki) and the association rate constant (kon) in vitro was investigated for eight different thrombin inhibitors. The carotid arteries of anaesthetized rats were exposed to FeCl3 for 1 h, and the thrombus size was determined from the amount of incorporated 125I- fibrinogen. The thrombin inhibitors were given intravenously, and complete concentration- and/or dose-response curves were constructed. Despite a 50,000-fold difference between the ki-values comparable plasma concentrations of hirudin and melagatran were needed (0.14 and 0.12 μmol 1-1, respectively) to obtain a 50% antithrombotic effect (IC50) in vivo. In contrast, there was a comparable in vitro (ki-value) and in vivo (IC50) potency ratio for melagatran and inogatran, respectively. These results can be explained by the concentration of thrombin in the thrombus and improved inhibition by the low-molecular-weight compounds. For all eight thrombin inhibitors tested, there was an inverse relationship between kon-values in vitro and the slope of the dose response curves in vivo. Inhibitors with kon-values of <1 X 107 M-1 s-1 gave steep dose response curves with a Hill coefficient >1. The association time for inhibition of thrombin for slow-binding inhibitors will be too long to give effective antithrombotic effects at low plasma concentrations, but at increasing concentrations the association time will decrease, resulting in a steeper dose-response curve and thereby a more narrow therapeutic interval.